A study on interspecific hybridization between piper nigrum and piper colubrinum - Chen, Yi Shang (Universiti Malaysia Sarawak, (UNIMAS), 2011)
ýInterspecific hybridization between P. nigrum L. and P. colubrinum Link. was attempted aiming to achieve Phytopthora foot rot resistant hybrid. P. nigrum, an important spice crop is tetraploid (2n=52) while P. colubrinum, a Phytopthora disease resistant species of Piper is diploid in nature. The main objective of this study is to find out the cross compatibility between the two species. Various experiments were conducted in this study i. e. reproductive biology study on parent plant, study on possible occurrence of apomixes in P. nigrum, artificial and natural pollination study and induction of tetraploid P. colubrinum. This study eventually proved that interspecific hybridization between P. nigrum L. and P. colubrinum Link) was incompatible by judging on negative result gathered from morphological and cytological studies on putative interspecific hybrid in first experiment of interspecific hybridization and zero success fruit set in second experiment of interspecific cross (after modified and improved methods of artificial pollination). There was also no germinati of P. nigrum in investigation of in vivo germination. Be interspecific hybridization, the studies were focused on developing a reliable method of artificial pollination between two species of Piper. Reproductive biology study on both parent plants i. e. P. nigrum (male) and P. colubrinum (female) enlightened that artificial pollination was ideally to be carried out approximately starting from 11 a. m until 5 p. m. In pollen viability study of P. colubrinum, anther dehiscence was discovered to occur around 9 a. m. and pollen was scientifically proved most viable at two hours after dehiscence and onward. Whilst, stigma receptivity study on P. nigrum suggested that stigma at stage I i. e. first emergence of stigmata and stage 3 i. e. complete emergence and wide spreading of stigmata were preferably to be selected for the hybridization. At the same time, apomixes was proved do not contribute to fruit set of P. nigrum. Besides reproductive biology study on both parent plants to assist artificial pollination, reliable methods of eliminating self pollination were also developed. A reliable method of eliminating self pollination can be achieved by sampled of single flower only per inflorescence together with bagging of inflorescence and physical emasculation. The applicability of these methods was proved practical. Eventually, chromosome doubling of P. colubrinum through colchicine was carried out as one of the possible solution for the cross incompatibility between P. nigrum and P. colubrinum. However, preliminary results showed the treatment was not successful. None of the colchicine treated plant (on shoot tip) showed positive results by judging on the cytological study. In vitro polyploidization that had been initiated also showed negative result. All the colchicine treated somatic embryos of P. colubrinum encounter blackening after the treatment. However, effort of inducing tetraploid P. colubrinum should be continued in future by using other antimitotic agent like oryzalin and trifluralin.